LITERATURE REVIEW PENGARUH KELENGKAPAN ADMINISTRASI PEMBELAJARAN TERHADAP KINERJA GURU DI MADRASAH - Chaerany, Chesia (Yayasan Panca Bakti Wiyata Pangandaran, 2024)
A study of the literature on the comprehensive impact of learning administration management on madrasa teacher performance is examined in this article. A major component of success in the teaching and learning process is teacher performance, which encompasses lesson planning, execution, and assessment. Teachers can carry out their teaching responsibilities in a more organized and methodical way with the help of institutional support and administrative duties that are part of effective learning administration. Nonetheless, some madrasas encounter challenges with administrative management, including a lack of technology support and administrative responsibilities that restrict instructional time. The quality of learning may suffer as a result of this barrier since it lowers instructor performance. This study employs a literature review methodology, gathering information from a range of electronic books and periodicals that address teacher performance and learning administration. The analysis's findings demonstrate that competent management, particularly when it comes to time and resource management, has a favorable effect on teachers' motivation and performance. Teachers can concentrate on instructional activities and student competency development when they have enough administrative support. In addition, the study's findings highlight how crucial it is for educational establishments to have a well-organized administrative structure in order to boost teacher professionalism and establish a high-quality learning environment. This study recommends improving the administration system in madrasas through increasing technological support and teacher training in learning administration management, so that teacher performance can be optimal and educational goals can be achieved optimally.